The Influence of Profitability, Company Size and Leverage on Company Value - Hidayat, Imam; Wati, Dwi Setia (Universitas Pamulang, 2022)
This study aims to explain the significance of the effect of profitability, company size and leverage partially on the value of property companies listed on the IDX. This study took a sample of 10 companies during the research period, namely 2018-2020 using the purposive sampling method with the criteria of sub-food & beverage manufacturing companies listed on the IDX during the 2018-2020 period . Sources of data used in this study is secondary data. Multiple linear regression is a data analysis technique used in this study. After testing, the results obtained that profitability and leverage partially have a significant effect on firm value, while the variable firm size does not affect the value of the company.